Case Report: Hodgkin Lymphoma and Refractory Systemic Lupus Erythematosus Unveil Activated Phosphoinositide 3-Kinase-δ Syndrome 2 in an Adult Patient - Conti, Francesca; Catelli, Arianna; Cifaldi, Cristina; Leonardi, Lucia; Mulè, Rita; Fusconi, Marco; Stefoni, Vittorio; Chiriaco, Maria; Rivalta, Beatrice; Di Cesare, Silvia; Schifino, Gioacchino; Sbrega, Fabiana; et al. (Frontiers in Pediatrics, 2021)
Introduction: Activated phosphoinositide 3‐kinase-δ syndrome 2 (APDS2) is a rare primary immune regulatory disorder caused by heterozygous gain of function mutation in the PIK3R1 gene encoding PI3Kδ regulatory p85 subunit and resulting in PI3Kδ hyperactivation. Clinical features range from recurrent infections to manifestations of immune dysregulation like autoimmunity, inflammation, systemic lymphoproliferation, and increased risk of cancer. We describe a new dominant PIK3R1 mutation causing APDS2 presenting with lymphoma and systemic refractory autoimmunity. Case presentation: A 30-year-old woman was referred to the Immunology Unit of our hospital for uncontrolled systemic lupus erythematosus, including chilblains lesions, systemic lymphoproliferation and IgA deficiency. At 19 years of age, she was diagnosed with Hodgkin’s lymphoma. Subsequently, she presented systemic lupus erythematosus onset, with episodes of severe exacerbation, including autoimmune hemolytic anemia and pleuro-pericarditis. Initial clinical response to conventional treatments was reported. Immunological investigations performed during our first observation showed severe lymphopenia, IgA deficiency, elevated IgM with reduced IgG2 levels, and low vaccination antibody titers. Quantitative real-time polymerase chain reaction (PCR) assay for Cytomegalovirus and Epstein‐Barr virus showed low viral loads for both viruses in serum. An increase of serum inflammatory markers highlighted persistent systemic hyperinflammation. The next-generation sequencing (NGS)‐based gene panel tests for primary immunodeficiency showed a heterozygous A>G substitution in the splice acceptor site at c.1300-2 position of PIK3R1, leading to exon-skipping. Conclusion: This case emphasizes the importance of suspecting primary immune regulatory disorders in young adults, predominantly showing a severe, aggressive, and refractory to treatment immune dysregulation phenotype, even in the absence of major infectious diseases at the onset. Different treatments can be promptly started, and a delayed diagnosis can highly impact the outcome. Targeted therapy against PI3Kδ pathway defect effectively improves drug-resistant autoimmunity, lymphoproliferation, and risk of progression to malignancy; eligible patients could benefit from its use even as a bridge therapy to transplantation, currently the only definitive curative treatment in eligible patients. Therefore, identifying genetic mutation and prompt targeted treatment is essential to control disease manifestations, prevent long-term sequelae, and enable curative HSCT in APDS2 patients.